A comment on the paper 'A comparison between lesions found during meat inspection of finishing pigs raised under organic/free-range conditions and conventional indoor conditions' by Alban et al. 2015. Issue 1 (December 2016) - Sørensen, Jan
Abstract This is a critical comment on a paper published in Porcine Health Management in 2015, presenting a comparison between lesions from meat inspection at one abattoir on slaughter pigs classified in to two different production forms: organic/free-range conditions and conventional indoor conditions. The conclusion made by the paper that 13 lesion types has a higher prevalence in organic/free-range pigs and 4 lesion types occurred less frequently in organic/free-range finishers compared to conventional finishers is correct except that 5 (instead of 4) lesion types occurred less frequently in organic/free-range finishers. However, these five types of lesions represent 74 % of all lesions recorded among conventional indoor, conventional free-range and organic pigs in one slaughter house from October 1 2012 to September 26 2013.